A contrastive study of conceptual metaphor related to “sea”/ “biển” in english and vietnamese songs - Huỳnh Thị Mỹ Dung (2015)
This study aims at conducting a contrastive analysis of conceptual metaphor related to “Sea”/ “Biển” in English and Vietnamese songs in the light of cognitive linguistics. The descriptive and contrastive methods are used in combination with the qualitative and quantitative approaches in order to help the researcher achieve the aims and objectives proposed. The data was taken from 500 songs in both English and Vietnamese with 400 samples of conceptual metaphors related to “Sea”/ “Biển” in total. We have figured out 9 conceptual metaphors related to “Sea”/ “Biển” in both languages. The study has pointed out the similarities as well as the differences of conceptual metaphors related to “Sea”/ “Biển” in English and Vietnamese. Besides giving an in-depth understanding of conceptual metaphors related to “Sea”/ “Biển” in both languages, the research is carried out with the hope of adding the voice to the variety of conceptual metaphors. In addition, implications of the thesis could be a useful reference for those who are interested in teaching and learning conceptual metaphors.